2016
DOI: 10.1080/02640414.2016.1215491
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cadence selection on peak power and time of power production in elite BMX riders: A laboratory based study

Abstract: The aims of this study were to analyse the optimal cadence for peak power production and time to peak power in bicycle motocross (BMX) riders. Six male elite BMX riders volunteered for the study. Each rider completed 3 maximal sprints at a cadence of 80, 100, 120 and 140revs·min -1 on a laboratory Schoberer Rad Messtechnik (SRM) cycle ergometer in isokinetic mode. The riders' mean values for peak power and time of power production in all three tests were recorded. The BMX riders produced peak power (1105± 139W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…For instance, in track cycling a faster acceleration can improve positioning, whereupon fewer meters have to be made. Furthermore, elite BMX riders continuously search for the optimal strategy to improve time to reach peak Beetroot juice and sport level 531 power (Rylands, Roberts, Hurst, & Bentley, 2017), as the athlete first at the curve very often is the winner.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in track cycling a faster acceleration can improve positioning, whereupon fewer meters have to be made. Furthermore, elite BMX riders continuously search for the optimal strategy to improve time to reach peak Beetroot juice and sport level 531 power (Rylands, Roberts, Hurst, & Bentley, 2017), as the athlete first at the curve very often is the winner.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, previous research performing all-out running on a non-motorized treadmill demonstrated a similar difference in P max between running and cycling [39]. In cycling, a high initial force has to be applied on the pedals, which might delay an increase in pedal frequency and cause a longer t pmax in cycling compared to running [30]. V La max was found to be higher in running ( + 25 %) with a large standard deviation ( ± 47 %) and poor correlation (R 2 = 17.4 %) between modalities.…”
Section: Differences Between Modalitiesmentioning
confidence: 93%
“…Riders in this study reached peak cadence of 212 ± 4 revs.min −1 with peak power of 2087 ± 156 W. Debraux et al 18 analysed peak power and cadence during the 80-m sprint test and reported an optimal theoretical cadence of 122 ± 18 revs.min −1 that elicited peak power. In a laboratory-based study, Rylands et al 9 analysed the optimal cadence for peak power and time to peak power production, where each elite BMX rider completed three maximal sprints at a cadence of 80, 100, 120 and 140 revs.min −1 . These riders produced peak power (1105 ± 139 W) at 100 revs.min −1 and shortest time to power production were attained at 120 revs.min −1 in 2.5 ± 1.07 s. In the current study, riders’ average cadence was 100 ± 8 rev.min −1 , but peak power was achieved at higher cadence (131 ± 6 rev.min −1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The same issue applies for laboratory-based measures evaluating power production. 8,9 The lab results can evaluate the capacity, but it is unknown whether this is repeatable on the track. Clearly, there is the need for a more valid method of power output measurement in BMX racing.…”
Section: Introductionmentioning
confidence: 99%